Wicked Employers Are the Septic Wound for Safai Karamcharis: Unmasking the White Collar Criminals (Journal of Advances and Scholarly Researches in Allied Education, 2019)
After a seriatim discussions with the Safai Karamcharis since last 4 years from different corner of Odisha I felt “wicked employers are the septic wound for Safai Karamcharis”. Everyone is taking the plea of ‘untouchability’, ‘social stigma’, ‘demeaning and despicable occupation’, etc. Nobody is taking active part for their development. To the best of their ability State Government as well as Central Government tried for their upliftment. But the employers are never serious about their development. Their activities towards Safai Karamcharis always remain ineffective. They are facing many obstacles. Instead fight for justice they prefer to fight against starvation. Never tried to draw others sympathy. This article will help to identify the frontier white collar criminals, wicked employers, and business labour rackets to stop the shameful act. Also, this article will be helpful for entire society to eradicate social stigma about the Scavengers, Safai Karamcharis and their Dependants as well as to get refund of their self-acquired treasure globally.